Contribuciones hermenéuticas para tratar con la diversidad desde la lingüisticidad de la comprensión - Gende, Carlos Emilio (2021)
The observation of linguistic diversity is frequently used as a datum to explain cultural diversity. In this way, two types of experiences, very different in their mode of constitution, are homologized, making it impossible to derive valuable consequences that would help us understand them. We aim to, first of all, review the assumptions of this theoretical attitude, which describes language as a product, and then to present some features of Ricoeur's position, which assumes it as a process oriented towards understanding.